2019
DOI: 10.1159/000497825
|View full text |Cite
|
Sign up to set email alerts
|

Nail Involvement in Psoriatic Patients and Association with Onychomycosis: Results from a Cross-Sectional Study Performed in a Military Hospital in Tunisia

Abstract: Nail psoriasis has variable prevalence and heterogeneous aspects. Many of them could mimic onychomycosis (OM). It has been suggested that patients with nail psoriasis are at high risk of OM. The aim of our study was to determine the epidemiological and clinical characteristics of nail psoriasis and to estimate the frequency and the factors associated with OM in psoriatic patients. The studied group included 163 patients with psoriasis aged 18 years or older. Epidemiological and clinical data, as well as the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…One of the limitations of the present investigation was the lack of control group to compare the rate of onychomycosis in psoriatic patients and control population; nevertheless, the majority of fungal infections in our study belonged to the nail infections (52.2%). is is less than the nail involvement reported by Jendoubi et al [28] and Zargari et al [29] which were 71.2% and 69.5%, respectively. In line with our findings, nail pitting is the most common nail matrix involvement among psoriatic patients [30].…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…One of the limitations of the present investigation was the lack of control group to compare the rate of onychomycosis in psoriatic patients and control population; nevertheless, the majority of fungal infections in our study belonged to the nail infections (52.2%). is is less than the nail involvement reported by Jendoubi et al [28] and Zargari et al [29] which were 71.2% and 69.5%, respectively. In line with our findings, nail pitting is the most common nail matrix involvement among psoriatic patients [30].…”
Section: Discussionmentioning
confidence: 50%
“…High prevalence of onychomycosis among psoriatic patients may related to abnormal capillary unit in psoriatic nails that damages the immune defenses generally supplied by the intact hyponychium and the use of immunosuppressive agents among psoriatic patients. On the other hand, faster turnover of nails in psoriatic patients may be noticed as a significant defense mechanism against fungal invasion [28]. One of the limitations of the present investigation was the lack of control group to compare the rate of onychomycosis in psoriatic patients and control population; nevertheless, the majority of fungal infections in our study belonged to the nail infections (52.2%).…”
Section: Discussionmentioning
confidence: 75%
“…The prevalence of onychomycosis was reported to be 18% in patients with psoriasis and 9.1% in the non‐psoriatic population in a systematic review, 5 there are contradictions regarding the increased risk of onychomycosis 11,16 . The frequency of onychomycosis in psoriasis was determined as 49.1% 9 by Gallo et al and 57.89% by Alves et al 10 Jendoubi et al found the prevalence of onychomycosis in patients with psoriasis with nail findings to be 53% in the military population 17 . In this study, the fact that mycological examination was performed in every patient with nail disorder, whether it is compatible with onychomycosis or not, seems to be the primary reason for the detection of onychomycosis at a lower frequency than those found in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Shemer et al [23] and Jendoubi et al [24] found that T. rubrum was by far the most common dermatophyte cultured from toenails. The only study that observed a similar prevalence of dermatophyte onychomycosis (43.27%) and onychomycosis caused by yeasts (43.55%) in psoriatic patients was that performed by Gallo et al [25].…”
Section: Dermatophytes Supported To Be the Most Frequently Involved F...mentioning
confidence: 99%